Pertussis vaccination for healthcare workers: staff attitudes and perceptions associated with high coverage vaccination programmes in England. (August 2016) - Paranthaman, K.; McCarthy, N.; Rew, V.; van Zoelen, S.; Cockerill, L.
Highlights: Two hospitals implemented booster vaccination programmes in response to suspected staff exposure to pertussis. Perceived vulnerability of patients was the single most important reason for healthcare workers accepting vaccination. Pertussis vaccine uptake was high among those who had not received influenza vaccination the previous year. Self-reported adverse effect profile following vaccination was reassuring. Fourteen percent of staff reported a recent illness compatible with pertussis but had not notified occupational health.